Impact of Belt Road Initiative on Indonesia‘s Oil and Gas Trade - Rachmadi, Rafi; Puspitawati, Eka (Journal of International Relations on Energy Affairs, 2022)
The development of international trade is important to boost an economy. Economic integration is used by Indonesia to increase trade values. Belt Road Initiative (BRI) is a new integration that is usefull for Indonesia. Under BRI, the most frequently traded commdities are oil and gas. However, Indonesia should consider impacts of the integration on the trade of oil and gas. This study using a gravity model aims to analyse impact of BRI on Indonesia’s oil and gas trade and determinant factors in the trade. The result of this study shows that Indonesia get a trade diversion from BRI. Determinant factors influencing on Indonesia’s trade are GDP, distance, price and consumption. Indonesia should take more benefits of energy sectors particularly oil and gas from BRI.